2016
DOI: 10.1021/acs.orglett.6b01240
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indole-Substituted Indanones via Palladium(II)-Catalyzed Tandem Reaction of ortho-Electron-Deficient Alkynyl-Substituted Aryl Aldehydes with Indoles

Abstract: A Pd(OAc)2-catalyzed cyclization reaction of ortho-electron-deficient alkynyl-substituted aryl aldehydes with indoles was accomplished, providing an efficient and economical way to synthesize indole-substituted indanones. The electron-withdrawing group attached to the alkyne and the nucleophilic indole play important roles in the formation of the indanone ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Complexes 3a , b are interesting as they represent the first examples of structurally characterized η 3 - o -ethynylphenyl-carbonyl complexes. Similar ene-yne complexes have been previously suggested as reactive intermediates in reactions of ene-yne-carbonyl compounds catalyzed by species such as Pd­(OAc) 2 , ZnCl 2 , Ag + , and CuCl but have not been isolated or detected. Furthermore, reactions of OsCl 2 (PPh 3 ) 3 with terminal alkynes usually give products derived from isomerization of the alkynes to give vinylidene complexes or nucleophilic attack of PPh 3 on the alkynes .…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Complexes 3a , b are interesting as they represent the first examples of structurally characterized η 3 - o -ethynylphenyl-carbonyl complexes. Similar ene-yne complexes have been previously suggested as reactive intermediates in reactions of ene-yne-carbonyl compounds catalyzed by species such as Pd­(OAc) 2 , ZnCl 2 , Ag + , and CuCl but have not been isolated or detected. Furthermore, reactions of OsCl 2 (PPh 3 ) 3 with terminal alkynes usually give products derived from isomerization of the alkynes to give vinylidene complexes or nucleophilic attack of PPh 3 on the alkynes .…”
Section: Resultssupporting
confidence: 57%
“…For example, the 31 P{ 1 H} NMR spectrum of 3a showed a singlet peak at −14.2 ppm. The 13 15 ZnCl 2 , 16 Ag + , 17 and CuCl 18 but have not been isolated or detected. Furthermore, reactions of OsCl 2 (PPh 3 ) 3 with terminal alkynes usually give products derived from isomerization of the alkynes to give vinylidene complexes or nucleophilic attack of PPh 3 on the alkynes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generally, they involve transition metal catalysis. Lu and co-workers have shown a palladium-catalyzed synthesis of indole-substituted indanones from o -alkynylbenzaldehydes involving the nucleophilic attack of indoles followed by intramolecular cyclization (Scheme A) . Enders group has developed an organocatalytic protocol for the synthesis of chiral indole-substituted indanols from o -nitrovinylbenzaldehydes (Scheme B) .…”
Section: Introductionmentioning
confidence: 99%
“…A possible mechanism for the formation of 8a and 9a is provided in Scheme . The coordination of the silver catalyst to the triple bond of substrate 6a gives complex A which then undergoes a 5- exo-dig cyclization to produce the key intermediate B . The active oxonium ion B can be converted into β-diketone C via hydrolysis reaction in the presence of adventitious water ( path a ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the same group developed In­(OTf) 3 -catalyzed reactions of enynals with propynol or alkynes for generation of tricyclic indanone products . Han and Lu’s group reported that the implementation of nucleophilic acetic acid and indoles can afford isobenzofuran and indanone derivatives, respectively. Bull and Cao et al reported independently a metal-free synthesis of isoindolinone and indenamine derivatives when amine compounds were employed .…”
Section: Introductionmentioning
confidence: 99%